2017
DOI: 10.1016/j.appet.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

What makes people leave their food? The interaction of personal and situational factors leading to plate leftovers in canteens

Abstract: In order to provide a basis for the reduction of food losses, our study analyzes individual food choice, eating and leftover behavior in a university canteen by consideration of personal, social and environmental determinants. Based on an extended literature review, a structural equation model is derived and empirically tested for a sample of 343 students. The empirical estimates support the derived model with a good overall model fit and sufficient R values for dependent variables. Hence, our results provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 80 publications
8
104
1
Order By: Relevance
“…Males are more likely than females to continue eating when they are full and clear their plate and this is statistically significant at p <0.05. The results indicate that plate size positively influences the plate waste, it concurred with previous studies (Ferreira et al, 2013;Cohen et al, 2014;Berkowitz et al, 2016;Lorenz et al, 2017). Further, this research indicated that females strongly suggested that they are more influenced by plate size and more likely to waste food if they have a bigger plate.…”
Section: Take In Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…Males are more likely than females to continue eating when they are full and clear their plate and this is statistically significant at p <0.05. The results indicate that plate size positively influences the plate waste, it concurred with previous studies (Ferreira et al, 2013;Cohen et al, 2014;Berkowitz et al, 2016;Lorenz et al, 2017). Further, this research indicated that females strongly suggested that they are more influenced by plate size and more likely to waste food if they have a bigger plate.…”
Section: Take In Figuresupporting
confidence: 90%
“…Therefore, varied portion sizes and plate sizes, palatable food, and providing food waste related information in the canteen serving area may reduce consumer-related food waste (Aschemann-Witazel et al, 2016;Lorenz et al, 2017).…”
mentioning
confidence: 99%
“…Generally, the TPB is a behavioral model that has extensively been applied for individual health and food related behaviors [29,[34][35][36][37][38]. It states that behavior can be determined by measuring behavioral intention [39].…”
Section: Derivation Of Research Hypothesesmentioning
confidence: 99%
“…In the service, or consumption stage, food waste is caused by the customer, who leaves the food on their plate. However, restaurants and caterers can also play a part in the generation of this waste, since they often serve too large portion sizes, or offer their food buffet-style (Kallbekken and Saelen 2013, Priefer, Jörissen et al 2016, Lorenz, Hartmann et al 2017. Offering buffet-style diners, encourages customers to take more than they can eat, leading to more leftovers on their plates.…”
Section: Hospitality and Catering Sectormentioning
confidence: 99%